Core Mold Machinery Optimization Process CNC Milling Machine - Fayi Rahmat Prayogi; Sesmaro Max Yuda; Bantu Hotsan Manullang (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
Global competition for the same product segmentation, companies need to innovate and optimize the products they produce. One of the optimizations carried out is by improving the machining process in the manufacture of mold components. The program creation process is carried out using Computer Aided Manufacturing (CAM) software from Delcam (PowerMill 2020) which is then used on CNC Milling machines. An improvement process is needed for making a CAM program so that production quality continues to meet standards and the production process time becomes more effective. To optimize the mold production process, reduce mold production costs, maintain the quality of the resulting production. By collecting data obtained by interacting directly with irrational parties, conducting experiments and directly observing the operational processes carried out in research, so as to understand the problems, critical points in the field. There are several factors that have an impact on research, namely on the quality that the quality of the product when viewed from the stock model is smooth and according to standards. Then delivery (Delivery) reduced machining time or cycle time on Core parts will provide reciprocal delivery to the next process at a more appropriate time. For the safety of the Computer Aided Manufacturing (CAM) program and the use of overhangs, if verified using PowerMill Software, no collisions or program crashes were found. It can be ascertained that the manufacturing program in this study is safe to use and the productivity obtained is more optimal.